2001
DOI: 10.1093/ajcn/73.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial responses of individual fatty acids in subjects homozygous for the threonine- or alanine-encoding allele in codon 54 of the intestinal fatty acid binding protein 2 gene

Abstract: The threonine-encoding allele of the FABP2 gene is associated with an increased postprandial response of 14-18-carbon fatty acids but not with changes in the relative amounts of individual fatty acids introduced to chylomicron triacylglycerols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 20 publications
1
32
0
1
Order By: Relevance
“…The possible mechanism through which the A54T polymorphism causes renal disease has not been established but might be related to endothelial dysfunction and glomerular damage due to higher levels of saturated fatty acids. Moreover, this polymorphism has also been associated with insulin resistance (19 -21) and higher levels of triglycerides in the fasting state and after a fatty meal challenge (18,22). In the present study, the association of the TT genotype with elevated triglycerides was only evident among patients without renal function impairment (serum creatinine Ͻ1.5 mg/dl).…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…The possible mechanism through which the A54T polymorphism causes renal disease has not been established but might be related to endothelial dysfunction and glomerular damage due to higher levels of saturated fatty acids. Moreover, this polymorphism has also been associated with insulin resistance (19 -21) and higher levels of triglycerides in the fasting state and after a fatty meal challenge (18,22). In the present study, the association of the TT genotype with elevated triglycerides was only evident among patients without renal function impairment (serum creatinine Ͻ1.5 mg/dl).…”
Section: Discussionsupporting
confidence: 46%
“…The A54T polymorphism of the FABP2 gene has been associated with an increase in FABP2 affinity for longchain fatty acids such as stearic and palmitic acids and consequently with higher levels of these fatty acids after a test meal (18). We have previously reported that patients with type 2 diabetes and microalbuminuria had higher levels of saturated fatty acids, especially stearic and palmitic acids, than normoalbuminuric patients (12).…”
Section: Discussionmentioning
confidence: 98%
“…In the latter study, Pima Indians may have other genetic predispositions to develop insulin resistance. In oral fatloading tests in adults, the postprandial response of 14-18-carbon FAs in chylomicron and VLDL triacylglycerols was significantly elevated in Thr54 homozygotes, whereas the amount of 20-and 22-carbon PU- 29) . In the high-fat meal test, plasma insulin level was significantly higher immediately after the meal in Thr54 subjects, although there were no significant differences in either glucose or triglyceride responses 28) .…”
Section: Discussionmentioning
confidence: 88%
“…In our study, the elevation of CRP in individuals with Thr allele could be related to an altered postprandial re- [31] . Elevated free fatty acids increase the accumulation of triglycerides in the adipocyte, related with imbalance of lipoprotein lipase activity and overproduction of adipokines such as IL-6 inducing high levels of CRP [32] .…”
Section: Discussionmentioning
confidence: 50%